1984
DOI: 10.1159/000206411
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic Diathesis in Multiple Myeloma

Abstract: Hemorrhage occurs during the clinical course in 15% of patients with multiple myeloma. We recently treated a patient with myeloma who had postoperative bleeding and hematuria despite normal coagulation parameters and platelet count. Platelet function studies revealed markedly abnormal aggregation to all stimulants. Plasma exchange successfully reversed in vitro and in vivo bleeding abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Previous reports indicate that bleeding occurs in approximately 15% of patients with IgG and more than 30% of patients with IgA and IgM M proteins . Bleeding was not directly evaluated by the authors of this study; therefore, the incidence of bleeding in this cohort is not known.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Previous reports indicate that bleeding occurs in approximately 15% of patients with IgG and more than 30% of patients with IgA and IgM M proteins . Bleeding was not directly evaluated by the authors of this study; therefore, the incidence of bleeding in this cohort is not known.…”
Section: Discussionmentioning
confidence: 80%
“…Increased risk of venous thromboembolism in myeloma patients is associated with increased FVIII and von Willebrand factor activity , decreased protein S activity , and acquired resistance to activated protein C . Bleeding occurs in approximately 15% of patients with IgG and more than 30% of patients with IgA and IgM M proteins . Secondary hemostatic defects that result in bleeding diathesis are due to a variety of mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…According to some researchers, this number can reach 15% [23,24]. However, in a group of 43 patients (MM-35, non-Hodgkin's lymphoma grade 3, WM-3 and MGUS-2), laboratory hemostatic disorders occurred in 60% of the examinees, and in 11% symptoms of bleeding were apparent [14,25].…”
Section: Discussionmentioning
confidence: 99%
“…These include: (a) interference of paraproteins with the normal function of coagulation factors (b) enhanced clearance of coagulation factors by the reticuloendothelial system; (c) anticoagulant activity of paraproteins; (d) abnormal platelet function; (e) excessive fibrinolysis; and (f) hyperviscosity per se . [ 2 3 ] In addition, a series of case reports demonstrated that acquired hemophilia A and acquired von Willebrand syndrome can cause severe bleeding in MM patients. [ 4 ] In our case, the coagulopathy was probably multifactorial.…”
Section: Discussionmentioning
confidence: 99%